Saltbush (Atriplex nummularia and A. amnicola) as potential plants for free-range layer farms: consequences for layer performance, egg sensory qualities, and excreta moisture. (28th May 2019) - de Koning, Carolyn; Barekatain, Reza; Singh, Mini; Drake, Kelly
ABSTRACT: Highly adapted plant species suited to low rainfall conditions need to be considered for free-range poultry farms, particularly in marginal rainfall areas. A group of suitable plants are the saltbushes, in particular old man saltbush ( Atriplex nummularia ) can provide shelter, shade, and possibly forage. The first experiment examined whether hens eat old man saltbush while ranging. Free-range Hy-Line Brown layer hens were provided saltbush or "no" saltbush on the outdoor range throughout 11 wk of early production (16 to 27 wk). The quantity of saltbush eaten by the hens was determined by the n -alkane method. Hen interactions with saltbush were video recorded, and hen live weight, feed intake, egg production, and egg quality were measured. Hens ate the saltbush at 5% of their dietary dry matter intake. This level of saltbush intake had no influence on egg production. The video footage revealed hens actively pecked at the saltbush. The second experiment investigated the consequences of hens diluting their diet by eating increased levels of River saltbush ( Atriplex amnicola ). Air-dried, hammer-milled river saltbush was mixed and pelleted into a standard commercial layer diet at the following levels; 0 (control), 5, 10, 15, and 20%. Hy-Line Brown layer hens were fed the diets for 28 D (32 to 35 wk of age). Seventy-five hens were housed in individual cages, with 15 hen replicates per diet. The saltbush had no significant impact on egg production, hen live weight, or feed intake. Excreta moisture increased significantly ( P < 0.001) with increased saltbush (5, 10, 15, and 20%) in the diet. Furthermore, high saltbush eggs (20%) had significantly stronger egg yolk color ( P = 0.006) and thicker egg shells ( P < 0.001) compared to the control eggs. Consumers were presented with the eggs from the second experiment and they preferred the high saltbush eggs (20%). In conclusion, saltbush would be a valuable plant on free-range poultry farms to provide shade and shelter, especially in those areas with marginal rainfall.